The impact of aggressive behavior of patients on staff employed in psychiatric wards - Sternal, Danuta; Gaweł, Dariusz; Bąk, Ewelina (Journal of Education, Health and Sport, 2023)
Introduction: Aggression and violence in the workplace are phenomena that occur more and more often, especially towards the staff working in Psychiatric Wards. The effects of these behaviors may be disturbances in the sphere of professional, social and mental health of employees. Aim of the study: The aim of the study was to analyze the phenomenon of patient aggression, to determine the frequency of patients' aggressive behavior and to assess their impact on the staff. Material and methods: The study was conducted among the staff working in the Bielsko Psychiatry Centre. The study used the diagnostic survey method, the research tool that was used in the work was a self-questionnaire. Results: Aggression of patients was experienced by 100% of the respondents. The most common manifestations of verbal aggression are vulgar words and shouting, and physical hitting and jerking. Physicians have less contact with physical aggression than other personnel. Despite this, most staff do not intend to change their place of employment and try to solve and prevent dangerous situations and minimize aggression on the part of patients with their professional approach to the patient. After attacks of aggression, the staff most often turns to a colleague for help and does not use the help of a psychologist. Conclusions: The analysis of the obtained data showed that aggression on the part of patients is a frequent phenomenon in the work of psychiatric ward staff.